Charge identification of fragments with the emulsion spectrometer of the FOOT experiment - Galati Giuliana (De Gruyter, 2021)
The FOOT (FragmentatiOn Of Target) experiment is an international project designed to carry out the fragmentation cross-sectional measurements relevant for charged particle therapy (CPT), a technique based on the use of charged particle beams for the treatment of deep-seated tumors. The FOOT detector consists of an electronic setup for the identification of Z≥3Z\ge 3 fragments and an emulsion spectrometer for Z≤3Z\le 3 fragments. The first data taking was performed in 2019 at the GSI facility (Darmstadt, Germany). In this study, the charge identification of fragments induced by exposing an emulsion detector, embedding a C2H4{{\rm{C}}}_{2}{{\rm{H}}}_{4} target, to an oxygen ion beam of 200 MeV/n is discussed. The charge identification is based on the controlled fading of nuclear emulsions in order to extend their dynamic range in the ionization response.